Acetate, a metabolic product of Heligmosomoides polygyrus, facilitates intestinal epithelial barrier breakdown in a FFAR2-dependent manner - Schälter, Fabian; Frech, Michael; Dürholz, Kerstin; Lucas, Sébastien; Sarter-Zaiss, Kerstin; Lebon, Luc; Esser-Von-Bieren, Julia; Dubey, Lalit Kumar; Vöhringer, David; Schett, Georg; Harris, Nicola L.; Zaiss, Mario (International Journal For Parasitology, 2022)

Alcohol-sourced acetate impairs T cell function by promoting cortactin acetylation - Azizov, Vugar; Hübner, Michel; Frech, Michael; Hofmann, Jörg; Kubankova, Marketa; Lapuente, Dennis; Tenbusch, Matthias; Guck, Jochen; Schett, Georg; Zaiss, Mario (iScience, 2023)
Alcohol is among the most widely consumed dietary substances. Excessive alcohol consumption damages the liver, heart, and brain. Alcohol also has strong immunoregulatory properties. Here, we report how alcohol impairs T cell function via acetylation of cortactin, a protein that binds filamentous actin and facilitates branching. Upon alcohol consumption, acetate, the metabolite of alcohol, accumulates in lymphoid organs. T cells exposed to acetate, exhibit increased acetylation of cortactin. Acetylation of cortactin inhibits filamentous actin binding and hence reduces T cell migration, immune synapse formation and activation. While mutated, acetylation-resistant cortactin rescues the acetate-induced inhibition of T cell migration, primary mouse cortactin knockout T cells exhibited impaired migration. Acetate-induced cytoskeletal changes effectively inhibited activation, proliferation, and immune synapse formation in T cells in vitro and in vivo in an influenza infection model in mice. Together these findings reveal cortactin as a possible target for mitigation of T cell driven autoimmune diseases.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Immunology; Molecular biology

An in vivo gene delivery approach for the isolation of reasonable numbers of type 2 innate lymphoid cells - Frech, Michael; Knipfer, Lisa; Wirtz, Stefan; Zaiss, Mario (MethodsX, 2020)
Group 2 innate lymphoid cells (ILC2s) are a recently recognized subset of innate lymphocytes with crucial role in mucosal immunity and tissue homeostasis. Over the past decade, substantial advances in our understanding of ILC2 biology have established them as an essential element in innate and adaptive immunity. However, their relatively low abundance and laborious purification from mucosal tissues make their study difficult. Moreover, due to a lack of an ILC2-specific Cre mouse-line, adoptive transfer of ILC2s into ILC-deficient hosts is inevitable. Herein we describe an in-depth protocol for the induction, isolation, and expansion of murine ILC2s. By combining an in vivo gene delivery approach to boost ILC2 numbers and a cell culture strategy to expand isolated cells, large quantities of highly pure ILC2s can be obtained. The isolated cells maintain their phenotype and can be used for subsequent cell transfer or in vitro studies. In comparison to previous protocols, this approach is cost-effective and efficient with potential yield of more than 20 million ILC2s isolated per mouse. • Group 2 innate lymphoid cells (ILC2s) are extensively studied in mouse models and humans in recent years. • Low abundance of ILC2s and current lack of specific ILC2 knockout mice makes in vivo research challenging. • This method allows high and pure ILC2 numbers for in vitro or adoptive in vivo transfer experiments.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Cell culture; Cytokines; Fluorescent activated cell sorting; Group 2 innate lymphoid cells; Isolation and expansion of murine ILC2s

Btn2a2 Regulates ILC2-T Cell Cross Talk in Type 2 Immune Responses - Frech, Michael; Omata, Yasunori; Schmalzl, Angelika; Wirtz, Stefan; Taher, Leila; Schett, Georg; Zaiss, Mario; Sarter, Kerstin (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILC) not only are responsible for shaping the innate immune response but also actively modulate T cell responses. However, the molecular processes regulating ILC-T cell interaction are not yet completely understood. The protein butyrophilin 2a2 (Btn2a2), a co-stimulatory molecule first identified on antigen-presenting cells, has a pivotal role in the maintenance of T cell homeostasis, but the main effector cell and the respective ligands remain elusive. We analyzed the role of Btn2a2 in the ILC-T cell cross talk. We found that the expression of Btn2a2 is upregulated in ILC2 following stimulation with IL-33/IL-25/TSLP. In vitro and in vivo experiments indicated that lack of Btn2a2 expression on ILC2 resulted in elevated T cell responses. We observed an enhanced proliferation of T cells as well as increased secretion of the type 2 cytokines IL-4/IL-5/IL-13 following cocultures with Btn2a2-deficient ILC2. In vivo transfer experiments confirmed the regulatory role of Btn2a2 on ILC2 as Btn2a2-deficient ILC2 induced stronger T cell responses and prevented chronic helminth infections. Taken together, we identified Btn2a2 as a significant player in the regulation of ILC2-T cell interactions.
CRIS-Team WoS Importer:2022-02-18

Butyrophilin 2a2 (Btn2a2) expression on thymic epithelial cells promotes central T cell tolerance and prevents autoimmune disease: Btn2a2 promotes central tolerance - Frech, Michael; Danzer, Heike; Uchil, Pooja; Azizov, Vugar; Schmid, Eva; Schälter, Fabian; Dürholz, Kerstin; Mauro, Daniele; Rauber, Simon; Munoz Becerra, Luis; Taher, Leila; Ciccia, Francesco; et al. (Journal of Autoimmunity, 2023)
Butyrophilins are surface receptors belonging to the immunoglobulin superfamily. While several members of the butyrophilin family have been implicated in the development of unconventional T cells, butyrophilin 2a2 (Btn2a2) has been shown to inhibit conventional T cell activation. Here, we demonstrate that in steady state, the primary source of Btn2a2 are thymic epithelial cells (TEC). Absence of Btn2a2 alters thymic T cell maturation and bypasses central tolerance mechanisms. Furthermore, Btn2a2−/− mice develop spontaneous autoimmunity resembling human primary Sjögren's Syndrome (pSS), including formation of tertiary lymphoid structures (TLS) in target organs. Ligation of Btn2a2 on developing thymocytes is associated with reduced TCR signaling and CD5 levels, while absence of Btn2a2 results in increased TCR signaling and CD5 levels. These results define a novel role for Btn2a2 in promoting central tolerance by modulating TCR signaling strength and indicate a potential mechanism of pSS development.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Autoimmune disease; Autoimmunity; Butyrophilin 2a2 (Btn2a2); Central tolerance; Primary sjögren's syndrome (pSS); Thymic epithelial cells (TEC)

CCL19‐positive lymph node stromal cells govern the onset of inflammatory arthritis via tropomyosin receptor kinase - Schälter, Fabian; Azizov, Vugar; Frech, Michael; Dürholz, Kerstin; Schmid, Eva; Hendel, Anna; Sarfati, Ilann; Maeda, Yuichi; Sokolova, Maria; Miyagawa, Ippei; Focke, Kristin; Sarter-Zaiss, Kerstin; et al. (Arthritis and Rheumatology, 2024)
Objectives To assess the role of CCL19+ lymph node stromal cells of the joint draining popliteal lymph node (pLN) for the development of arthritis. Methods CCL19+ lymph node stromal cells were spatiotemporally depleted for 5 days in the pLN before the onset of collagen-induced arthritis (CIA) using Ccl19-Cre x iDTR mice. In addition, therapeutic treatment with recombinant CCL19-IgG, locally injected in the footpad, was used to confirm the results. RNA sequencing of lymph node stromal cells combined with T cell co-culture assays using tropomyosin receptor kinase (Trk) family inhibitors together with in vivo local pLN siRNA treatments were used to elucidate the pathway by which CCL19+ lymph node stromal cells initiate the onset of arthritis. Results Spatiotemporal depletion of CCL19+ lymph node stromal cells prevented disease onset in CIA mice. These inhibitory effects could be mimicked by local CCL19-IgG treatment. The mRNA sequencing analyses showed that CCL19+ lymph node stromal cells downregulated the expression of the tropomyosin receptor kinase A (TrkA) just before disease onset. Blocking TrkA in lymph node stromal cells led to increased T cell proliferation in in vitro co-culture assays. Similar effects were observed with the pan-Trk inhibitor Larotrectinib in co-cultures of lymph node stromal cells of rheumatoid arthritis patients and T cells. Finally, local pLN treatment with TrkA inhibitor and TrkA siRNA led to exacerbated arthritis scores. Conclusions CCL19+ lymph node stromal cells are crucially involved in the development of inflammatory arthritis. Therefore, targeting of CCL19+ lymph node stromal cells via TRK kinases could provide a tool to prevent arthriti

Ethanol consumption inhibits TFH cell responses and the development of autoimmune arthritis - Azizov, Vugar; Dietel, Katharina; Steffen, Franziska; Dürholz, Kerstin; Meidenbauer, Julia; Lucas, Sébastien; Frech, Michael; Omata, Yasunori; Tajik, Narges; Knipfer, Lisa; Kolenbrander, Anne; Seubert, Silvia; et al. (Nature Communications, 2020)
Alcohol consumption is a consistent protective factor for the development of autoimmune diseases such as rheumatoid arthritis (RA). The underlying mechanism for this tolerance-inducing effect of alcohol, however, is unknown. Here we show that alcohol and its metabolite acetate alter the functional state of T follicular helper (TFH) cells in vitro and in vivo, thereby exerting immune regulatory and tolerance-inducing properties. Alcohol-exposed mice have reduced Bcl6 and PD-1 expression as well as IL-21 production by TFH cells, preventing proper spatial organization of TFH cells to form TFH:B cell conjugates in germinal centers. This effect is associated with impaired autoantibody formation, and mitigates experimental autoimmune arthritis. By contrast, T cell independent immune responses and passive models of arthritis are not affected by alcohol exposure. These data clarify the immune regulatory and tolerance-inducing effect of alcohol consumption.
CRIS-Team Scopus Importer:2020-05-05

Inflammatory Arthritis and Bone Metabolism Regulated by Type 2 Innate and Adaptive Immunity - Omata, Yasunori; Frech, Michael; Saito, Taku; Schett, Georg; Zaiss, Mario; Tanaka, Sakae (International Journal of Molecular Sciences, 2022)
While type 2 immunity has traditionally been associated with the control of parasitic infections and allergic reactions, increasing evidence suggests that type 2 immunity exerts regulatory functions on inflammatory diseases such as arthritis, and also on bone homeostasis. This review summarizes the current evidence of the regulatory role of type 2 immunity in arthritis and bone. Key type 2 cytokines, like interleukin (IL)-4 and IL-13, but also others such as IL-5, IL-9, IL-25, and IL-33, exert regulatory properties on arthritis, dampening inflammation and inducing resolution of joint swelling. Furthermore, these cytokines share anti-osteoclastogenic properties and thereby reduce bone resorption and protect bone. Cellular effectors of this action are both T cells (i.e., Th2 and Th9 cells), but also non-T cells, like type 2 innate lymphoid cells (ILC2). Key regulatory actions mediated by type 2 cytokines and immune cells on both inflammation as well as bone homeostasis are discussed.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Osteoclast; Rheumatoid arthritis; Type 2 immunity; Type 2 innate lymphoid cells

Microbiota-Derived Propionate Modulates Megakaryopoiesis and Platelet Function - Dürholz, Kerstin; Schmid, Eva; Frech, Michael; Azizov, Vugar; Otterbein, Nadine; Lucas, Sébastien; Rauh, Manfred; Schett, Georg; Bruns, Heiko; Zaiss, Mario (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is associated with an increased risk for cardiovascular events driven by abnormal platelet clotting effects. Platelets are produced by megakaryocytes, deriving from megakaryocyte erythrocyte progenitors (MEP) in the bone marrow. Increased megakaryocyte expansion across common autoimmune diseases was shown for RA, systemic lupus erythematosus (SLE) and primary Sjögren’s syndrome (pSS). In this context, we evaluated the role of the microbial-derived short chain fatty acid (SCFA) propionate on hematopoietic progenitors in the collagen induced inflammatory arthritis model (CIA) as we recently showed attenuating effects of preventive propionate treatment on CIA severity. In vivo, propionate treatment starting 21 days post immunization (dpi) reduced the frequency of MEPs in the bone marrow of CIA and naïve mice. Megakaryocytes numbers were reduced but increased the expression of the maturation marker CD61. Consistent with this, functional analysis of platelets showed an upregulated reactivity state following propionate-treatment. This was confirmed by elevated histone 3 acetylation and propionylation as well as by RNAseq analysis in Meg-01 cells. Taken together, we identified a novel nutritional axis that skews platelet formation and function.
CRIS-Team Scopus Importer:2022-08-05
Keywords: hematopoietic progenitors; megakaryocytes; microbiota; platelets; rheumatoid arthritis; short-chain fatty acids

Microbiota-derived propionate modulates megakaryopoiesis and platelet function - Schmid, Erik; Dürholz, Kerstin; Frech, Michael; Otterbein, N.; Lucas, Sébastien; Rauh, Manfred; Schett, Georg; Bruns, Heiko; Zaiss, Mario (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Microbiota-induced Intestinal Barrier Dysfunction Initiates the Shuttling of Immune Cells from the Gut to the Joints - Tajik, Narges; Frech, Michael; Brandl, Carolin; Canete, Juan; Ciccia, Francesco; Schett, Georg; Zaiss, Mario (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Propionate induced bacterial-derived histamine promotes resolution of synovial inflammation - Dürholz, Kerstin; Lucas, Sébastien; Schmid, Eva; Schaelter, F.; Frech, Michael; Azizov, Vugar; Hofmann, Jörg; Iljazovic, A.; Strowig, T.; Taudte, Verena; Fromm, Martin; Xiang, Wei; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

RANKL-Induced Btn2a2 – A T Cell Immunomodulatory Molecule – During Osteoclast Differentiation Fine-Tunes Bone Resorption - Frech, Michael; Schuster, Gregor; Andes, Fabian T.; Schett, Georg; Zaiss, Mario; Sarter, Kerstin (Frontiers in Endocrinology, 2021)
Butyrophilins, which are members of the extended B7 family of immunoregulators structurally related to the B7 family, have diverse functions on immune cells as co-stimulatory and co-inhibitory molecules. Despite recent advances in the understanding on butyrophilins’ role on adaptive immune cells during infectious or autoimmune diseases, nothing is known about their role in bone homeostasis. Here, we analyzed the role of one specific butyrophilin, namely Btn2a2, as we have recently shown that Btn2a2 is expressed on the monocyte/macrophage lineage that also gives rise to bone degrading osteoclasts. We found that expression of Btn2a2 on monocytes and pre-osteoclasts is upregulated by the receptor activator of nuclear factor κ-B ligand (RANKL), an essential protein required for osteoclast formation. Interestingly, in Btn2a2-deficient osteoclasts, typical osteoclast marker genes (Nfatc1, cathepsin K, TRAP, and RANK) were downregulated following RANKL stimulation. In vitro osteoclast assays resulted in decreased TRAP positive osteoclast numbers in Btn2a2-deficient cells. However, Btn2a2-deficient osteoclasts revealed abnormal fusion processes shown by their increased size. In vivo steady state µCT and histological analysis of bone architecture in complete Btn2a2-deficient mice showed differences in bone parameters further highlighting the fine-tuning effect of BTN2a2. Moreover, in rheumatoid arthritis patients and experimental arthritis, we detected significantly decreased serum levels of the secreted soluble Btn2a2 protein. Taken together, we identified the involvement of the immunomodulatory molecule Btn2a2 in osteoclast differentiation with potential future implications in basic and translational osteoimmunology.
CRIS-Team Scopus Importer:2021-08-27
Keywords: bone homeostasis; bone resorption; osteoclast (OC); RANKL (receptor activator for nuclear factor k B ligand); T cell

Regulation of bone and joint inflammation by type 2 innate lymphoid cells - Omata, Yasunori; Zaiss, Mario; Frech, Michael; Schett, Georg; Tanaka, Sakae (Elsevier, 2023)
The innate and adaptive immune systems regulate inflammation in arthritis. The innate immune system works as one of the “first responders” against the invasion of pathogens, followed by adaptive immunity activation. The cross-talk between innate and adaptive immune cells has protective roles against pathogens and induces immunological responses. Recently, a new type of innate immune cells, innate lymphoid cells (ILCs), was discovered; it was found that they play a profound role in immunological responses. ILCs function closely with T helper cells, depending on their respective subsets. In this chapter, we mainly focus on one subset, type 2 ILCs (ILC2s), and review their role in inflammatory arthritis and bone homeostasis.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Adaptive immunity; Arthritis; Bone; Innate immunity; Innate lymphoid cells (ILC); Osteoclast; T cell

Targeting intestinal tight junctions to inhibit onset of arthritis - Tajik, N.; Schulz, O.; Frech, Michael; Lucas, Sébastien; Sarter-Zaiss, Kerstin; Schett, Georg; Zaiss, Mario (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Targeting zonulin and intestinal epithelial barrier function to prevent onset of arthritis - Tajik, Narges; Frech, Michael; Schulz, Oscar; Schälter, Fabian; Lucas, Sébastien; Azizov, Vugar; Dürholz, Kerstin; Steffen, Franziska; Omata, Yasunori; Rings, Andreas; Bertog, Marko; Rizzo, Aroldo; et al. (Nature Communications, 2020)
Gut microbial dysbiosis is associated with the development of autoimmune disease, but the mechanisms by which microbial dysbiosis affects the transition from asymptomatic autoimmunity to inflammatory disease are incompletely characterized. Here, we identify intestinal barrier integrity as an important checkpoint in translating autoimmunity to inflammation. Zonulin family peptide (zonulin), a potent regulator for intestinal tight junctions, is highly expressed in autoimmune mice and humans and can be used to predict transition from autoimmunity to inflammatory arthritis. Increased serum zonulin levels are accompanied by a leaky intestinal barrier, dysbiosis and inflammation. Restoration of the intestinal barrier in the pre-phase of arthritis using butyrate or a cannabinoid type 1 receptor agonist inhibits the development of arthritis. Moreover, treatment with the zonulin antagonist larazotide acetate, which specifically increases intestinal barrier integrity, effectively reduces arthritis onset. These data identify a preventive approach for the onset of autoimmune disease by specifically targeting impaired intestinal barrier function.
CRIS-Team Scopus Importer:2020-05-05

The role of Butyrophilin 2a2 (Btn2a2) in T cell maturation - Frech, Michael; Uchil, P.; Azizov, Vugar; Schober, K.; Irla, M.; Sarter, Kerstin; Zaiss, Mario (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

The Role of Dietary Fiber in Rheumatoid Arthritis Patients: A Feasibility Study - Häger, Julian; Bang, Holger; Hagen, Melanie; Frech, Michael; Träger, Pascal; Sokolova, Maria V.; Steffen, Ulrike; Tascilar, Koray; Sarter, Kerstin; Schett, Georg; Rech, Jürgen; Zaiss, Mario (Nutrients, 2019)
Short-chain fatty acids are microbial metabolites that have been shown to be key regulators of the gut-joint axis in animal models. In humans, microbial dysbiosis was observed in rheumatoid arthritis (RA) patients as well as in those at-risk to develop RA, and is thought to be an environmental trigger for the development of clinical disease. At the same time, diet has a proven impact on maintaining intestinal microbial homeostasis. Given this association, we performed a feasibility study in RA patients using high-fiber dietary supplementation with the objective to restore microbial homeostasis and promote the secretion of beneficial immunomodulatory microbial metabolites. RA patients (n = 36) under routine care received daily high-fiber bars or cereals for 28 days. Clinical assessments and laboratory analysis of immune parameters in blood and stool samples from RA patients were done before and after the high-fiber dietary supplementation. We observed an increase in circulating regulatory T cell numbers, favorable Th1/Th17 ratios, as well as decreased markers of bone erosion in RA patients after 28 days of dietary intervention. Furthermore, patient-related outcomes of RA improved. Based on these results, we conclude that controlled clinical studies of high-fiber dietary interventions could be a viable approach to supplement or complement current pharmacological treatment strategies.
CRIS-Team Scopus Importer:2019-10-18
Keywords: gut–joint axis; high-fiber diet (HFD); microbiota; rheumatoid arthritis (RA); short chain fatty acids (SCFA)

The role of joint-draining lymph node stromal cells in inflammatory arthritis - Schälter, Fabian; Azizov, Vugar; Frech, Michael; Dürholz, Kerstin; Sokolova, Maria; Hendel, Anna; Focke, Kristin; Sarter-Zaiss, Kerstin; Van Baarsen, L. G. M.; Krautwald, S.; Schett, Georg; Zaiss, Mario (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Type 2 innate lymphoid cells inhibit the differentiation of osteoclasts and protect from ovariectomy-induced bone loss - Omata, Yasunori; Frech, Michael; Lucas, Sébastien; Primbs, Tatjana; Knipfer, Lisa; Wirtz, Stefan; Kadono, Yuho; Saito, Taku; Tanaka, Sakae; Sarter, Kerstin; Schett, Georg; Zaiss, Mario (Bone, 2020)
While the role of T cells in the regulation of bone homeostasis is well defined, little is known about the role of innate lymphoid cells (ILCs) on bone. ILCs are innate immune cells that share cytokine expression patterns with T cells but lack the T cell receptor. In this study we show that type 2 ILCs (ILC2) potently inhibit the generation of bone resorbing osteoclasts in vitro as well as favorably influence bone homeostasis under steady state conditions in vivo using loss and gain of function models. Furthermore, adoptive transfer of ILC2 completely abrogated ovariectomy-induced bone loss by significantly down-regulating osteoclast numbers in vivo. The suppressive effects of ILC2s on osteoclasts in vitro and in vivo as well as the protection from ovariectomy-induced bone loss were linked to their expression of IL-4 and IL-13 as well as STAT6 activation on the myeloid target cell, since deletion of IL-4/IL-13 in ILC2s or STAT6 in osteoclast precursors abrogated the anti-osteoclastogenic effect of ILC2s. Taken together, these findings show that ILC2 have to be considered as potent regulators of bone homeostasis.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Bone loss; Cytokines; ILC2; Osteoclasts; Osteoimmunology; Type 2 innate lymphoid cells type